STRATEGI MITIGASI RISIKO UNIT PEMASARAN DI ERA DIGITALISASI PADA SEGMEN BISNIS (B2B) PT TELKOM INDONESIA TBK [MARKETING UNIT RISK MITIGATION STRATEGIES IN THE ERA OF DIGITALIZATION AT BUSINESS SEGMENT (B2B) PT TELKOM INDONESIA TBK] - Yuliwulansih, Haryani; Mulyani, Kahar (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2025)
The rapid advancement of the digital era and the continuously shifting market dynamics have created significant challenges for marketing functions, particularly in addressing technological disruptions and changes in consumer behavior. As a leading telecommunication company facing intense market competition, Telkom Indonesia continuously strives to adapt to evolving market conditions, which exposes the company to various types of risks. This article examines the range of marketing risks in the telecommunications sector within the digital era, including market volatility, digital data security, and shifting consumer trends. Employing a literature review approach and utilizing contemporary risk management frameworks, this study highlights marketing technology adaptation and consumer data management as key solutions to mitigate risks in the Business-to-Business (B2B) telecommunications marketing segment.